Application of Morals Education towards the Family, Moral towards Neighbors and Moral towards the Environment - Ida Marina Harahap; Sapri Sapri; Ira Suryani (Universitas Muhammadiyah Enrekang, 2023)
Ethical education plays a crucial role in shaping a civilized society. This research aims to design and develop an educational application focusing on three main aspects: family morality, neighborly ethics, and environmental morality. The application is designed to provide a holistic understanding of moral values and ethics that strengthen interpersonal relationships in various social contexts. Firstly, the focus on family morality education provides a profound insight into the importance of values such as understanding, justice, and love in the context of household relationships. The application offers multimedia and interactive resources that support the learning of children and parents to create a harmonious family environment. Secondly, in the development of neighborly ethics, the application emphasizes solidarity, tolerance, and mutual respect among members of the local community. Through engaging lesson modules, users are encouraged to understand their role in fostering good neighborly relations and contributing to the formation of a better community. Lastly, the application explores the concept of environmental morality, highlighting the significance of sustainability and social responsibility towards nature. The educational modules provide practical information and actions to motivate users in preserving their surroundings, promoting environmentally friendly behaviors, and supporting sustainability initiatives. Utilizing modern technology, this application offers an interactive and engaging approach to help society comprehend and internalize ethical values in everyday life. It is hoped that the implementation of this application can positively contribute to character formation and have a beneficial impact on the harmony levels within families, neighborhoods, and the surrounding environment.